Large -scale wheat flour folic acid fortification program increases plasma folate levels among women of reproductive age in urban Tanzania. - Ramadhani A Noor; Ajibola I Abioye; Nzovu Ulenga; Salum Msham; George Kaishozi; Nilupa S Gunaratna; Ramadhani Mwiru; Erin Smith; Christina Nyhus Dhillon; Donna Spiegelman; Wafaie Fawzi (PLoS ONE)
There is widespread vitamin and mineral deficiency problem in Tanzania with known deficiencies of at least vitamin A, iron, folate and zinc, resulting in lasting negative consequences especially on maternal health, cognitive development and thus the nation's economic potential. Folate deficiency is associated with significant adverse health effects among women of reproductive age, including a higher risk of neural tube defects. Several countries, including Tanzania, have implemented mandatory fortification of wheat and maize flour but evidence on the effectiveness of these programs in developing countries remains limited. We evaluated the effectiveness of Tanzania's food fortification program by examining folate levels for women of reproductive age, 18-49 years. A prospective cohort study with 600 non-pregnant women enrolled concurrent with the initiation of food fortification and followed up for 1 year thereafter. Blood samples, dietary intake and fortified foods consumption data were collected at baseline, and at 6 and 12 months. Plasma folate levels were determined using a competitive assay with folate binding protein. Using univariate and multivariate linear regression, we compared the change in plasma folate levels at six and twelve months of the program from baseline. We also assessed the relative risk of folate deficiency during follow-up using log-binomial regression. The mean (±SE) pre-fortification plasma folate level for the women was 5.44-ng/ml (±2.30) at baseline. These levels improved significantly at six months [difference: 4.57ng/ml (±2.89)] and 12 months [difference: 4.27ng/ml (±4.18)]. Based on plasma folate cut-off level of 4 ng/ml, the prevalence of folate deficiency was 26.9% at baseline, and 5% at twelve months. One ng/ml increase in plasma folate from baseline was associated with a 25% decreased risk of folate deficiency at 12 months [(RR = 0.75; 95% CI = 0.67-0.85, P<0.001]. In a setting where folate deficiency is high, food fortification program with folic acid resulted in significant improvements in folate status among women of reproductive age.